Partitioning beta diversity in a tropical karst seasonal rainforest in Southern China. Issue 1 (December 2018) - Guo, Yili; Xiang, Wusheng; Wang, Bin; Li, Dongxing; Mallik, Azim; Chen, Han; Huang, Fuzhao; Ding, Tao; Wen, Shujun; Lu, Shuhua; Li, Xiankun
Abstract Both deterministic and stochastic processes have been linked to forest community assembly; however, their contribution to beta diversity has not been properly explored, and no studies to date have investigated their impacts on sparse depleted soils in forests that contain widespread exposed limestone karst. We found that the pairwise differences in species composition between quadrates was determined by a balanced variation in abundance, whereby the individuals of some species at one site were substituted by an equivalent number of individuals of different species at another site. Both the total beta diversity and its balanced variation in abundance declined with increasing sampling grain size. Our research indicated that environmental differences exert a strong influence on beta diversity, particularly total beta diversity and its balanced abundance variation in larger grain sizes. It was evident that deterministic and stochastic processes worked together, and that deterministic processes were more important than stochastic processes in the regulation of beta diversity in this heterogeneous tropical karst seasonal rainforest of Southern China. However, in future research a functional trait based approach will be required to tease out the relative degree of deterministic and stochastic processes toward an assessment of the temporal changes in species composition.